Hybrid PV–VAWT Automatic Fish Feeding System for Sustainable Aquaculture - Aulia, M Habib; Dewi, Tresna; Bow, Yohandri (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study developed and experimentally evaluated an automatic fish feeding system powered by a hybrid photovoltaic (PV)–Vertical Axis Wind Turbine (VAWT) energy architecture for small-scale aquaculture applications. The prototype integrated PV generation, a VAWT, battery storage, charge control, a DC–AC inverter, a programmable timer, and an auger-based feeding mechanism. An engineering Design and Development approach was applied through prototype design, assembly, laboratory testing, and field evaluation. VAWT performance was evaluated under controlled laboratory conditions and at two field environments, Lubuk Bakung and Tanjung Api-Api Port, while PV performance was assessed with and without the feeder load. The two automatic feeder units required a combined electrical power of 52 W. The PV subsystem produced a maximum of 76.85 W without feeder load and 60.80 W under feeder load, providing an 8.80-W (16.9%) instantaneous margin above feeder demand at peak output. VAWT maximum power reached 17.304 W in the laboratory, 17.93 W at Tanjung Api-Api, and 0.689 W at Lubuk Bakung, demonstrating substantial site-dependent variation in wind-energy contribution. Battery input voltage remained within 12.4–12.6 V during the Lubuk Bakung observations, while the inverter supplied 208–218 V AC under the tested light-load condition. The feeding mechanism completed the observed programmed cycles without mechanical interruption or pellet blockage. Overall, the findings demonstrate the technical feasibility of a PV-dominant, VAWT-supplemented, battery-buffered architecture for autonomous automatic fish feeding under the tested conditions.